2004
DOI: 10.1080/10715760410001717327
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Restores Lifespan of Superoxide-dismutase Deficient Yeast

Abstract: Yeast (Saccharomyces cerevisiae) mutants lacking CuZn-superoxide dismutase (CuZnSOD) are hypersensitive to oxygen and have significantly decreased replicative life span. Both these defects can be ameliorated by exogenous ascorbate. The effect of ascorbate on life span is complicated by auto-oxidation of its compound in the medium. If negative effects of auto-oxidation are prevented by exchange of the medium, ascorbate prolongs not only mean but also maximal replicative life span of the yeast in the atmosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…Similar results have already been obtained for hamster cells exposed to L-ascorbic acid. 19 Of interest, Krzepilko et al 20 have recently shown that ascorbate can restore the life-span of sod1 mutants and that this protection is probably due to the scavenging of the radical superoxide. In the same way, sod1∆ was protected by L-ascorbic acid against oxidative damage induced by paraquat, as observed in Figure 2.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results have already been obtained for hamster cells exposed to L-ascorbic acid. 19 Of interest, Krzepilko et al 20 have recently shown that ascorbate can restore the life-span of sod1 mutants and that this protection is probably due to the scavenging of the radical superoxide. In the same way, sod1∆ was protected by L-ascorbic acid against oxidative damage induced by paraquat, as observed in Figure 2.…”
Section: Discussionmentioning
confidence: 98%
“…The prooxidative effects of some antoxidants revealed in the cellular tests may contribute to the limited effectiveness of the in vivo applications of antioxidants [32 -34] and be a complication of the use of yeast as a test system for antioxidants [1] (Zyracka et al, submitted). On the other hand, the cellular system of testing antioxidants may allow for a preselection of antioxidant compounds which are of potential therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that ascorbate is able to protect Saccharomyces cerevisiae lacking CuZn-superoxide dismutase (SOD1) against toxicity of pure oxygen atmosphere, shortening of replicative life span [1] and auxotrophy for lysine and methionine (Zyracka et al, submitted). Ascorbate restored also growth of Dsod1 mutant on a hypertonic medium, alleviating the effect of hypertonicity mediated by oxidative stress.…”
Section: Introductionmentioning
confidence: 97%
“…This effect is mediated by oxidative stress, since the SOD1Δ strain is oversensitive to hypertonic medium compared to wild-type yeast, and ROS accumulate in yeast cells exposed to hypertonic media (Garay-Arroyo et al, 2003;Koziol et al, 2005). These obvious phenotypes of SOD1Δ could be reversed by the addition of L-ascorbic acid (AsA), a potent antioxidant (Krzepilko et al, 2004;Zyracka et al, 2005a;Koziol et al, 2005, Saffi et al, 2006. Compensation of the Sod1 defect by an antioxidant implies that the mutant yeast can be used as a biosensor to antioxidants (Zyracka et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%